Hubungan Antara Perceived Organizational Support Dengan Employee Wellbeing Pada Karyawan Di PT. X Majalaya - Anantha, Wilfried Dimas Yoga; Pratiwi, Endah Andriani (JURNAL PSIKOLOGI INSIGHT, 2022)
AbstractThis study aims to describe whether there is a significant relationship between Perceived Organizational Support and Employee Wellbeing of Employees at PT. X. This study uses a quantitative method, the type of research is correlational with a deductive approach. The research subjects consisted of 61 employees in the production department. The sampling technique used is total sampling. The data collection in this study used the Perceived Organizational Support Scale and the Employee Wellbeing Scale by distributing questionnaires to employees. Data processing uses Spearman rank correlation. The results showed that Spearman's rho was 0.678 and p-value under 0.001. Perceived Organizational Support and Employee Wellbeing had a significant and positive relationship, which means that the higher the Perceived Organizational Support, the higher the Employee Wellbeing.Keywords: company, employee wellbeing, employees, perception of organizational support, Abstrak Penelitian ini bertujuan untuk menggambarkan apakah terdapat hubungan yang signifikan antara Perceived Organizational Support dengan Employee Wellbeing pada Karyawan di PT. X. Penelitian ini menggunakan metode kuantitatif, jenis penelitian korelasional dengan pendekatan deduktif. Subjek penelitian terdiri dari 61 orang karyawan di bagian produksi. Teknik pengambilan sampel yang digunakan yaitu total sampling. Pengumpulan data pada penelitian ini menggunakan Skala Perceived Organizational Support dan Skala Employee Wellbeing dengan menyebarkan kuesioner pada karyawan. Pengolahan data menggunakan korelasi rank Spearman. Hasil penelitian menunjukkan bahwa spearman’s rho sebesar 0,678 dan p-value 0.001. Perceived Organizational Support dan Employee Wellbeing memiliki hubungan yang signifikan dan bersifat positif yang artinya semakin tinggi Perceived Organizational Support maka semakin tinggi pula Employee Wellbeing.Kata kunci:karyawan, kesejahteraan karyawan, persepsi dukungan organisasi, perusahaan